Peran Informasi Harga Dalam Mempengaruhi Keputusan Konsumen Di Pasar Mikro - Muhammad Khoirun Nasirin; Muhammad Syafi'i Budi Santoso; Syafiul Umam; M. Farid Al-Azhar (Faculty of Islamic Economics and Business, 2026)
This study aims to analyze the role of price information in influencing consumer decisions in micro markets. Price information is a crucial factor for consumers in making purchasing decisions, particularly in traditional markets, which tend to have varying degrees of information transparency. This study employed a descriptive qualitative method with a field study approach. Data were collected through in-depth interviews, observation, and documentation with consumers and micro-business owners. The results indicate that price information plays a significant role in shaping consumer perceptions of a product's value, influencing price comparisons, and determining purchasing decisions. Limited access to price information leads to information asymmetry, which results in suboptimal consumer decisions. Furthermore, direct interaction, such as bargaining, serves as an alternative mechanism for obtaining price information. This study implies that increasing price transparency and information access can promote micro market efficiency and improve consumer welfare.